Explaining Glossolalia Instead of Speaking in Tongues: Emotional Energy and Authority Relations at a Midwestern Pentecostal Megachurch - Freudenberg, Maren (Research in the social scientific study of religion, 2022)
Based on first-hand qualitative research in an Assemblies of God megachurch outside of Springfield, Missouri, the article examines the tension between different forms of authority at play in familiarizing congregants and newcomers with Pentecostal practices. Focusing on a prayer service held in September 2018 in which attendees were encouraged to speak in tongues, it investigates the fine balance between perpetuating the charismatic-Pentecostal tradition but not overwhelming newcomers unfamiliar with it. The pastor interprets both the success or failure of attendees to speak in tongues in a positive light by (1) framing glossolalia as a sign of divine election and (2) insisting that failure to speak in tongues does not imply divine rejection. This tension reveals the interplay of individual and communal, of personal and institutional authority at play, with ultimately reifying effects on the event’s power hierarchies.